ANALYSIS OF THE RELATIONSHIP OF PRODUCT QUALITY, SERVICE QUALITY, PRICES AND PROMOTIONS ON BUYING DECISION (STUDY AT NINE WALI MEDAN SHOPS) - Ramadhan Nurmuhammad; Endang Sulistya Rini; Amrin Fauzi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine and analyze the influence of product quality, service quality, price and promotion on purchasing decisions. The research location is Sembilan Wali Bookstore, Medan. The research method in this research is descriptive with a quantitative approach. The sample for this research is 100 consumers. The data analysis technique uses multiple linear regression analysis which is processed with the help of SPSS version 25 software. The results of the research show that Product Quality partially has a significant effect on the Purchasing Decision variable with a t value of > from t table, namely 2,411 > 1,660 and sig < alpha, namely 0.002 < 0.05. Service Quality partially has a significant effect on the Purchasing Decision variable with a value of tcount > from ttable, namely 3.105 > 1.660 and sig < alpha, namely 0.003 < 0.05. Price partially has a significant effect on the Purchasing Decision variable with a value of tcount > from ttable, namely 2,283 > 1,660 and sig < alpha, namely 0.020 < 0.05. Partial promotion does not have a significant effect on the Purchasing Decision variable with a value of tcount > ttable, namely 1.433 < 1.660 and sig > alpha, namely 0.066 > 0.05. Product Quality, Service Quality, Price and Promotion simultaneously have a significant effect on the Purchasing Decision variable with a value of Fcount > from Ftable, namely 3,439 > 2,306, while sig. < of alpha, namely 0.011 < 0.05. The contribution of the influence of the independent variable to the dependent variable is 35.6% and the remainder is influenced by other variables outside this research.